Lifelong self-education in a sociotechincal context - Gonzalo Vázquez Gómez (Universidad de La Rioja, 2020)
Permanent education is a process of self-construction based on the pedagogical principles of educability, educativity and personal autonomy. The process of human construction implies a process of lifelong and lifewide learning and training in order to achieve individual and community "well-being". This conception of continuing education includes the consideration of new learning spaces such as that of the cognitive city and new possibilities such as the open courses. Within the approach of capabilities building, the possibilities and risks of self-regulated learning are studied as an effective strategy in the current socio-technical and technological globalization context. Finally, the risk potential of the contribution of learning analytics and artificial intelligence (AI) to education is examined; and it is concluded that the process of permanent education in a socio-technical context must be based on a solid human formation conceived as basic education.